External validation of the ORBI risk score for cardiogenic shock prediction in patients with ST elevation myocardial infarction. (3rd May 2023) - Verdaguer, J; Denisi, N; Riche, M; Biendel, C; Lhermusier, T; Roncalli, J; Carrie, D; Elbaz, M; Bouisset, F; Delmas, C
Abstract: Funding Acknowledgements: Type of funding sources: Public hospital(s). Main funding source(s): CHU de Toulouse. Background: Cardiogenic shock (CS) complicates 5 to 15 % of ST-segment elevation myocardial infarction (STEMI) and is associated with high short-term mortality (up to 40-50%). The ORBI risk score (ORS) based on 11 variables was created in order to identify patients at high-risk of in-hospital STEMI-related CS but external validation is lacking. Purpose: To externally validate the ORBI risk score. Methods: Consecutive STEMI patients managed by percutaneous coronary intervention (< 24 h after chest-pain onset) in our tertiary hospital in 2019 were retrospectively included. Patients with CS at admission, with previous fibrinolysis or without PCI attempted were excluded. Data necessary for the calculation of the ORBI risk score were collected (age, prior stroke/transient ischaemic attack, cardiac arrest upon admission, type of STEMI, first medical contact-to-pPCI delay, initial clinical presentation, Killip class, heart rate, blood pressure, glycaemia, culprit lesion, and post-pPCI TIMI-flow grade) and the occurrence of in-hospital CS. Then we have tested the discrimination and the calibration of the score based of ROC curves and C-statistic analysis. Results: 287 patients were included (age 64 yo, 81.2% male, anterior STEMI 40.8%, LAD culprit lesion 47%, median first medical contact-to-PCI delay 112 min). The median ORBI-risk score was 4 (IQR 2-7) with 78% patients considered at low (ORS 0-7), 12.2% intermediate-low (ORS 8-10), 4.1% intermediate-high (11-12) and 5.6% high (ORS ≥13) risk. In-hospital CS occurred in 18 patients (6.3%) as compared with the predicted CS likelihood of 4.3 % signing a possible CS occurrence under-estimation. The AUC-ROC for CS prediction was 0.91 (CI95 %: 0.83-0.97) in our population. The best cut off was ≥ 10 (Se 77.7% and Spe 92%) allowing good classification of 93 % of patients. All-cause in-hospital mortality was 4.2%. Conclusions: Our study confirmed the good discrimination of the ORBI-risk score to predict CS occurrence in STEMI patients. The score is simple to use based on simple clinical and biological data available at patient admission and may help to adapt initial patient monitoring and management. Future dedicated studies are needed to test this hypothesis.